(untitled) (Damascus University Journal of agriculture sciences, 2021)
This research provides a method for hiding secret data in color images. The binary represatintation of characters of the secret message is divided into three parts by dividing the bits of the character into three parts, and every part is hidden in bits of each color of the three colors (RGB), which represents the colored image element. The characters of the secret message are embedded in non-sequential pixels, therefore the distance between characters is not constant. It will be difficult to quest the place of bits of character in the pixels by image analysis or statistical analysis methods. The method succeeded in hiding many types of text in different images without degrading or seeing any difference between the Stego image and the original image. Measures such as MSE, PSNR and NCC are used to prove the accuracy of the results and efficiency. The application implemented using Matlab 9.